Plano de projeto: Troca dos rotores de ar de tiragem dos fornos de Clinquer W1 e W2 - Lima, Chrystian George de (Universidade do Vale do Rio dos Sinos, 2014)
This paper aims to present the project plan exchange of rotors air circulation ovens W1 and W2. The project is developed in line with the requirements established by the sponsor. The project plan includes the following structure: management plans, integration, scope, time, cost, quality, resources, communications, risk and acquisitions that are necessary to the practice of project management, following the practices addressed in the PMBOK Guide
Keywords: Rotores de ar; Escopo; Rotors air; Planos de gerenciamento da integração; Management plans integration; Scope